The Examination of Type 2 Diabetes Patients' Acceptance of Disease and Self-Care Situations - Abdullah Gercek and Papatya Karakurt (Professor Despina Sapountzi-Krepia, 2024)
The Examination of Type 2 Diabetes Patients' Acceptance of Disease and Self-Care Situations